The Influence Of Education and Training On The Work Performance Employees Of Airport Andi Jemma Masamba, North Luwu Regency - Alfikri, Muh. Dimas; Sukri; Basir, Adil (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The aim of this study is to determine the influence of education and training on work performance inAndi Jemma Masamba Airport located in North Luwu Regency. Theoretically, this study strengthens the hypothesis that education and training significantly improve employee performance, and emphasizes the importance of competency development through education and training programs. Practically, it provides recommendations to office leaders to strengthen education and training programs as a strategy to improve employee performance and quality. The method used in this study is the survey method with a quantitative analysis approach. The sampling technique was carried out with total sampling. Data were obtained using descriptive test instruments and questionnaire instruments that had been tested for validity and reliability. The analysis techniques used were Validity Test Analysis, Reliability, Classical Assumptions, Multiple Linear Regression, t-test, f-test, and Determination Coefficient and correlation. The results showed that there was an influence of education and training on employee performance at Andi Jemma Masamba Airport, North Luwu Regency, this can be seen from the significance values of 0.008 and 0.000 which means less than 0.05.